DAMPAK UNDANG UNDANG CIPTA KERJA TERHADAP TENAGA KERJA DISABILITAS DALAM PEMUTUSAN HUBUNGAN KERJA - Surya Insani Kamil (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The Omnibus Law (Law No. 11 of 2020) is intended to create more job opportunities and attract investments by simplifying labor regulations. However, the implementation of this law may exacerbate the condition of workers with disabilities, a vulnerable group. This study aims to analyze the impact of the Omnibus Law on workers with disabilities in Indonesia, focusing on the protection of their labor rights. The findings indicate a significant dual impact, with the law potentially increasing their vulnerability to termination of employment (layoffs), particularly in more physically demanding sectors such as manufacturing and construction. Despite the legal obligation for companies to meet inclusivity standards for workers with disabilities, its implementation remains weak, with many workers facing layoffs due to productivity reasons or the company's inability to provide necessary accommodations. Furthermore, the absence of stronger post-layoff protection mechanisms worsens their situation. This study recommends improving the supervision of policy implementation and introducing specific protection mechanisms for workers with disabilities, particularly regarding layoffs and workplace accessibility.